Avaliação de parâmetros do metabolismo de carbono e nitrogênio e de respostas ao estresse na associação de trigo com a bactéria Herbaspirillum seropedicae - Ortolan, Sarah Romani (2015)
Wheat is considered the main cereal diet of the world population, but in recent years has achieved some gain in productivity of this culture despite having increased the use of nitrogen fertilizer. The use of plant growth promoting bacteria such as Herbaspirillum seropedicae SmR1 among others has been studied to obtain development of plants with less use of nitrogen fertilizers. However there is little information relating the effects of this interaction in plant development and grain yield. Objective of this study was to evaluate the carbon and nitrogen metabolism by certain enzymes, metabolites and indices related to the response to infectious stress on the wheat cultivars CD 104 and CD 120 in association with Herbaspirillum seropedicae bacteria. Two experiments were conducted. The experimental design was completely randomized with four replications in a 4x2. The first factor relates to the conditions inoculation with bacteria and/or nitrogen source in coverage are: control without inoculation with bacteria or added nitrogen fertilizer (C); application of nitrogen fertilizer (50 kg.ha-1) 30 days after sowing (N); inoculation with 106 cells of the bacterium H. seropedicae/seed at planting (Hs) and inoculation with bacteria combined with the application of nitrogen fertilizer (Hs + N) and the second factor refers to the phenological stages (tillering and booting). The results indicated that inoculation with H. seropedicae in wheat seeds of cv.s CD 104 and CD 120 in the two growth stages answered in relation to the indices related to stress with the involvement of enzymes of carbon and nitrogen metabolism. However prominent effect was not noticed to promote plant growth of wheat in late development, nor a deleterious effect of the bacterium for inoculation cv. CD 104 under the experimental conditions. For cv. CD 120 the differential effects indicate lower levels of stress and some level of association to positive effect on productivity when combined inoculation of bacteria to nitrogen fertilization. It was concluded that as well as pathogenic and stressors, H. seropedicae able to beneficially associate with wheat also provides similar interference pattern of carbon and nitrogen metabolism and stress levels